Combined IL-2 Immunocomplex and Anti-IL-5 mAb Treatment Expands Foxp3+ Treg Cells in the Absence of Eosinophilia and Ameliorates Experimental Colitis - Abo, Hirohito; Flannigan, Kyle L.; Geem, Duke; Ngo, Vu L.; Harusato, Akihito; Denning, Timothy L. (Frontiers in Immunology, 2019)
Interleukin (IL)-2 is expressed during T cell activation and induces the proliferation and differentiation of T cells. CD4+Foxp3+ regulatory T cells (Tregs) constitutively express the high affinity IL-2 receptor (CD25/IL-2R) and rapidly respond to IL-2 to elaborate numerous suppressive mechanisms that limit immune-mediated pathologies. Accumulating evidence supports the concept that an aberrant balance between Tregs and Teff contribute to the pathology of intestinal inflammation and that the IL-2/Treg axis is a potential pathway to exploit for the treatment of inflammatory bowel disease (IBD). Here, we show that treatment of mice with IL-2/IL-2 antibody (JES6-1) immunocomplex during DSS-induced colitis induced Foxp3+ Treg expansion, but also potently stimulated GATA3+ type 2 innate lymphoid cell (ILC2) proliferation and high-level expression of IL-5. Furthermore, IL-2/JES6-1 treatment resulted in massive eosinophil accumulation and activation in the inflamed colon, and afforded only modest protection from colitis. In light of these findings, we observed that combined IL-2/JES6-1 and anti-IL-5 mAb treatment was most effective at ameliorating DSS-induced colitis compared to either treatment alone and that this regimen allowed for Foxp3+ Treg expansion without concomitant eosinophilia. Collectively, our findings provide insight into how blockade of IL-5 may aid in optimizing IL-2 immunotherapy for the treatment of intestinal inflammation.